2017
DOI: 10.1186/s10194-017-0788-0
|View full text |Cite
|
Sign up to set email alerts
|

Headache attributed to airplane travel: diagnosis, pathophysiology, and treatment – a systematic review

Abstract: BackgroundHeadache attributed to airplane travel, also named "airplane headache" (AH) is a headache that occurs during take-off and landing. Today, there are still uncertainties about the pathophysiology and treatment of AH. This systematic review was performed to facilitate identification of the existing literature on AH in order to discuss the current evidence and areas that remain to be investigated in AH.MethodsThe systematic literature search was performed in 3 relevant medical databases; PubMed, Scopus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 49 publications
0
60
0
Order By: Relevance
“…Headache attributed to airplane travel (airplane headache (AH)) is a painful headache that occurs during the takeoff and/ or landing; however, the headache mostly appears during the landing [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There is still uncertainty about the treatment of AH, but the current literature indicates that pharmacological treatments such as triptans might be effective for AH [4]. We present a patient in Denmark who has used triptans with beneficial effects on AH.…”
Section: To the Editormentioning
confidence: 99%
“…Headache attributed to airplane travel (airplane headache (AH)) is a painful headache that occurs during the takeoff and/ or landing; however, the headache mostly appears during the landing [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There is still uncertainty about the treatment of AH, but the current literature indicates that pharmacological treatments such as triptans might be effective for AH [4]. We present a patient in Denmark who has used triptans with beneficial effects on AH.…”
Section: To the Editormentioning
confidence: 99%
“…The official insertion of AH in the international classification attracted the attention of the scientific community; subsequently and up until publication of this article, 45 publications in English on the topic have been published …”
Section: Historical Outlinementioning
confidence: 99%
“…It has been considered that barotrauma associated with trigeminal nerve endings in the ethmoid sinuses causes the frontoorbital pain in this clinical entity. [14][15][16] It has been speculated that the vasodilation in the cerebral arteries which developed during an AHAattack may be induced by prostaglandin E2. 14,17 Although there is no specific treatment or prophylaxis for AHA, it has been demonstrated that several medications including analgesics, nonsteroidal antiinflammatory drugs or triptans may have beneficial effects as prophylactic therapy.…”
mentioning
confidence: 99%
“…[14][15][16] It has been speculated that the vasodilation in the cerebral arteries which developed during an AHAattack may be induced by prostaglandin E2. 14,17 Although there is no specific treatment or prophylaxis for AHA, it has been demonstrated that several medications including analgesics, nonsteroidal antiinflammatory drugs or triptans may have beneficial effects as prophylactic therapy. However, drugs and nasal spray decongestants should be taken prophylactically approximately 30 minutes and 30-60 minutes, respectively before the expected triggering phase (ascending or descending phase) of the flightto obtain optimal results.…”
mentioning
confidence: 99%
See 1 more Smart Citation